ANALISIS PERSON JOB FIT DAN PERSON ORGANIZATION FIT SERTA PENGARUHNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI DI HOTEL MELIA BALI INDONESIA - Stella Sinthya Dewi; Ida Bagus Putu Suamba; I Wayan Siwantara (Cahaya Ilmu Bangsa, 2024)
An organization within a company cannot function without the assistance of human resource management (HRM). The HRM within the company generally needs to be well-maintained and carefully considered. This research was conducted on the contract employees of Melia Bali Indonesia, the aim of this research is to determine how person-job fit and person-organization fit affect organizational citizenship behavior with organizational commitment as a mediator among employees of Melia Bali Indonesia. This study is a descriptive quantitative research with a sample of 141 respondents. Data collection techniques in this research used questionnaires and were assisted by SmartPLS. Testing in the SEM analysis shows that the direct effects of the Person-Job Fit variable on Organizational Citizenship Behavior have a T-statistic value of 5.730 or more than 1.96. Meanwhile, the Person-Organization Fit variable on Organizational Citizenship Behavior has a T-statistic value of 11.087 or more than 1.96. Additionally, the results of the indirect effects of the Person-Job Fit and Person-Organization Fit variables on Organizational Citizenship Behavior through Organizational Commitment are not significant. This research concludes that the independent variables directly and significantly affect the dependent variable without the need for the intervening variable. Keywords: Person Job Fit, Person Organization Fit, Organizational Citizenship Behavior, Organization Commitment